Analisis Budaya dalam Pembelian Perabotan Rumah Tangga secara Kredit Pada Keluarga Mampu di Desa Buatan II menurut Perspektif Ekonomi Syariah - Rinaldi, Afdhol; Safitri, Anisa (MUI Kota Pekanbaru, 2023)
This research is motivated by the large number of well-off families who still buy household furniture on credit in Artificial Village II. This makes researchers interested in researching further the reasons why families are able to still buy goods on credit. The problem studied is how cultural factors influence the purchase of household furniture on credit among well-off families and what is the opinion of Sharia Economics regarding rich families who use credit to buy furniture for their homes. Field research uses qualitative field methods The data required for this situation is the buyer (well-off family) and seller who completed the credit trade exchange in Artificial Village II. Observations, interviews and documentation were used to obtain data. Analysis of qualitative descriptive data from this research reveals that cultural factors are the main reason why people in Artificial Village II can buy household furniture on credit. Many people in Artificial Village II do not understand what cultural factors exist in society, so without realizing it, culture is the main cause of people buying goods on credit. Islam does not forbid this strategy of buying and selling on credit because it can make it easier for people to get the goods they need because they don't need to spend money for it. That the support and conditions framed by Islam should be adhered to in carrying out trade exchanges to ensure harmony between associations and arrangements without any pressure.